Minor heavy metal: A review on occupational and environmental intoxication - Wiwanitkit, Viroj (Medknow Publications, 2008)
Heavy metal is widely used in industries and presents as a problematic environmental pollution. Some heavy metals, especially lead and mercury, are well described for their occupational and environmental intoxication whereas the other minor heavy metals are less concerned. In this article, the author will present the details of occupational and environmental minor heavy metal intoxication. This review focuses mainly on aluminum, tin, copper, manganese, chromium, cadmium and nickel.